Analisis Nilai Sosial dan Nilai Budaya dalam Kanal YouTube “Dongeng Kita” serta Pemanfaatannya sebagai Bahan Ajar Bahasa dan Sastra Sastra Indonesia di SMA - Aisah, Siti (Jurnal Artikula, 2025)
This research analyzes the social and cultural values in the YouTube channel "Dongeng Kita" edition of Banten and West Java folk tales, as well as its use as teaching material for Indonesian Language and Literature in high school. This research was carried out based on a qualitative approach with descriptive methods that focused on content analysis. Based on the research results, it was found that the social values in these folk tales include compassion, responsibility and harmony in life. These values support the formation of student character, such as caring, discipline and harmony. Apart from that, analysis of cultural values shows that there are values related to humans' relationships with God, nature, fellow humans and themselves. These cultural values are important in strengthening students' local identity and increasing their understanding of Indonesia's cultural heritage. The use of folklore from the YouTube channel "Dongeng Kita" as teaching material is considered effective in increasing student involvement in learning. Interesting animated content makes it easier for students to understand the material, while the social and cultural values conveyed through folklore are relevant to character formation and cultural education in schools. By using digital media, this research concludes that the integration of folklore into Indonesian Language and Literature learning in high school can provide a more contextual, interesting learning experience and support the preservation of local culture